All Questions Topic List
Algebra Questions
Previous in All Question Next in All Question
Previous in Algebra Next in Algebra
Question Number 199671 by Mingma last updated on 07/Nov/23
Answered by mr W last updated on 07/Nov/23
a1=3,a2=9⇒a0=−1an=an−1+an+12−1⇒(an+1−an)=(an−an−1)+2letbn=an−an−1⇒bn+1=bn+2⇒A.P.⇒bn=b1+2(n−1)b1=a1−a0=3−(−1)=4⇒an−an−1=4+2(n−1)=2n+2∑nn=1(an−an−1)=2×n(n+1)2+2nan−a0=2×n(n+1)2+2n⇒an=n2+3n+a0=n2+3n−1✓n2+3n−1=2023n2+3n−2024=0n=−3+9+4×20242≈43.5a43=432+3×43−1=1977✓
Commented by Mingma last updated on 07/Nov/23
Perfect ��
Terms of Service
Privacy Policy
Contact: info@tinkutara.com